Zakat as an Instrument of Economic Redistribution: Perspectives of Islamic Law and Indonesian Positive Law - Purwanti Purwanti; Nur Arifudin (Dinasti Publisher, 2026)
This comprehensive research delves into the crucial role of zakat as a mechanism of economic redistribution, by examining fundamentally its theoretical foundations and practical implementation through two main lenses: Islamic Law and Indonesian Positive Law. This research is motivated by the ongoing challenges of economic inequality in Indonesia, a Muslim-majority country, and seeks to explore how zakat, which is a pillar of Islamic economics, can be optimized as a formal instrument of fiscal and social policy within a modern national legal framework. Within the framework of Indonesian Positive Law, this study documents a significant legal transformation. The ratification of Law Number 23 of 2011 concerning the Management of Zakat represents a formal